Musyarakah mutanaqishah Pada Perbankan Syariah di Indonesia: Pendekatan Maqasid Syariah - Yarmunida, Miti (Institut Agama Islam Bengkulu, 2020)
This study aims to identify the implementation of the musyarakah mutanaqishah contract in Islamic banking in Indonesia based on the Islamic maqasid review. This research uses descriptive qualitative method. The research data were collected using the documentation method. The data used in this research is secondary data obtained from various sources regarding the provisions of sharia fatwas, sharia standards, statutory regulations, operational and practical standards in Islamic banking, as well as the results of relevant research and publications. The data were analyzed using the inductive method. The analysis of the implementation of the musyarakah mutanaqishah contract is carried out based on the maqasid sharia approach. The results of the study found that the implementation of the musyarakah mutanaqishah contract as an alternative to mudharabah financing in Islamic banking, from the aspect of risk charging and equal partnerships, was not in accordance with the maqashid sharia and existing regulations in Indonesia